COCOMO Method for Planning Human Resources in Software Development - Nátz, Katalin; Vinovgradov , Szergej; Szalay, Zsigmond Gábor (Acta Carolus Robertus, 2023)
Over the past decades, software development has been a priority project for business leaders. Compared to the production or purchase of a productive asset, IT development could be carried out at a lower cost, and controlling always found a hidden reserve that could be used for this purpose.But this process is in transition at the beginning of the 21st century. IT projects should be examined early in the development phase to determine the functional size of a software application and to determine the business value and expenditure that the application represents for a particular segment of the business. However, process analysis and productivity and cost analysis of these developments are more challenging than average for business analysts.Enterprise information systems are evolving very rapidly, and their user base is growing. These applications handle so much data and are so complex that it is difficult for the average user to understand how they work. New coding tools are now enabling software developers to meet growing and increasingly complex customer needs more efficiently and quickly. A comprehensible, comparable, and clear method for interpreting, estimating, and verifying projects is needed.
Keywords: function point; COCOMO; effort estimation